2005
DOI: 10.1021/ac050724z
|View full text |Cite
|
Sign up to set email alerts
|

Congruent Strategies for Carbohydrate Sequencing. 1. Mining Structural Details by MSn

Abstract: This report is the first in a series of three focused on establishing congruent strategies for carbohydrate sequencing. The reports are divided into (i) analytical considerations that account for all aspects of small oligomer structure by MS n disassembly, (ii) database support using an ion fragment library and associated tools for highthroughput analysis, and (iii) a concluding algorithm for defining oligosaccharide topology from MS n disassembly pathways. The analytical contribution of this first report expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
229
0
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(243 citation statements)
references
References 39 publications
7
229
0
3
Order By: Relevance
“…The branching pattern of the oligosaccharides could be deduced from CID spectra containing fragments bearing a mass signature of Ϫ14 Da for each lost branch. In samples containing Hex and HexNAc residues, abundant 0,4 A, 1,4 A, 1,3 A, and 3,5 A cross-ring fragments were often observed, thus allowing the assignment of 1-2, 1-4, and 1-6-linkages [37,38]. Elimination at the C3 of HexNAc was also observed, and provided a chemical signature that could be used to assign C3 substitutions as has been previously reported [17,18].…”
Section: Rationale and Key Experimental Observationssupporting
confidence: 55%
See 1 more Smart Citation
“…The branching pattern of the oligosaccharides could be deduced from CID spectra containing fragments bearing a mass signature of Ϫ14 Da for each lost branch. In samples containing Hex and HexNAc residues, abundant 0,4 A, 1,4 A, 1,3 A, and 3,5 A cross-ring fragments were often observed, thus allowing the assignment of 1-2, 1-4, and 1-6-linkages [37,38]. Elimination at the C3 of HexNAc was also observed, and provided a chemical signature that could be used to assign C3 substitutions as has been previously reported [17,18].…”
Section: Rationale and Key Experimental Observationssupporting
confidence: 55%
“…Online derivatization coupled with LC/MS of permethylated oligosaccharide alditols has obvious advantages, and we are in the process of adapting online derivatization to the LC/MS platform. Reinhold et al have recently reported the complete assignment of oligosaccharide structures of permethylated glycans using a database library, FragLib, in conjunction with their Oligosaccharide Subtree Constraint Algorithm (OSCAR) [38,54,55]. This algorithm incorporates analyst-selected MS n ion fragmentation pathways for elucidation of oligosaccharide topology using a top-down sequencing strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In these examples, we will use many of the concepts and tools previously described. 7,8,15,[26][27][28] All structures were derived de novo with input data from a single instrument.…”
Section: Resultsmentioning
confidence: 99%
“…A large body of work has shown that spectral comparisons of isomers at different stages of sequential molecular fragmentation (MS n ) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] are clearly different, although in one case, reproducibility has been reported to be "vague". 25 In our experience, spectral reproducibility has been excellent, 26 and this very feature has provided an opportunity to build a searchable fragment library 27 and derive glycan structure with supporting tools. 28 It has been effectively argued that the transfer of energy by gas-phase collisions maybe too broad to define the subtle isomeric features within carbohydrate structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation